Current source with low voltage controlled for surface electrical stimulation - Masdar, Aizan (2013)
Functional Electrical Stimulation (FES) is a promising way to restore mobility to Spinal Cord Injury (SCI) patients by applying low-level electrical current to the paralyzed muscles so as to enhance that person’s ability to function and live independently. However, due to the limited number of commercially available FES assisted exerciser systems and their rather high cost, the conventional devices are unaffordable for most peoples. Thus, this paper makes a comparative study of the various design of a multiple purpose portable functional electrical stimulator which is used in surface stimulation for patients with spinal cord injuries. The functionality, circuit performance and reliability of the circuits are presented.